Overexpression of AaWRKY1 Leads to an Enhanced Content of Artemisinin in Artemisia annua. (23rd February 2016) - Jiang, Weimin; Fu, Xueqing; Pan, Qifang; Tang, Yueli; Shen, Qian; Lv, Zongyou; Yan, Tingxiang; Shi, Pu; Li, Ling; Zhang, Lida; Wang, Guofeng; Sun, Xiaofen; et al.
Abstract : Artemisinin is an effective component of drugs against malaria. The regulation of artemisinin biosynthesis is at the forefront of artemisinin research. Previous studies showed that AaWRKY1 can regulate the expression of ADS, which is the first key enzyme in artemisinin biosynthetic pathway. In this study, AaWRKY1 was cloned, and it activated ADSpro and CYPpro in tobacco using dual-LUC assay. To further study the function of AaWRKY1, pCAMBIA2300-AaWRKY1 construct under 35S promoter was generated. Transgenic plants containing AaWRKY1 were obtained, and four independent lines with high expression of AaWRKY1 were analyzed. The expression of ADS and CYP, the key enzymes in artemisinin biosynthetic pathway, was dramatically increased in AaWRKY1- overexpressing A. annua plants. Furthermore, the artemisinin yield increased significantly in AaWRKY1- overexpressing A. annua plants. These results showed that AaWRKY1 increased the content of artemisinin by regulating the expression of both ADS and CYP . It provides a new insight into the mechanism of regulation on artemisinin biosynthesis via transcription factors in the future.